2003
DOI: 10.1017/s1049023x00001291
|View full text |Cite
|
Sign up to set email alerts
|

Variables Influencing Medical Usage Rates, Injury Patterns, and Levels of Care for Mass Gatherings

Abstract: Objectives:Mass gatherings create difficult environments for which to plan emergency medical responses. The purpose of this study was to identify those variables that are associated with increased medical usage rates (MURs) and certain injury patterns that can be used to facilitate the planning process.Methods:Patient information collected at three types of mass gatherings (professional American football and baseball games and rock concerts) over a three-year period was reviewed retrospectively. Specific varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
99
3
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(116 citation statements)
references
References 33 publications
13
99
3
1
Order By: Relevance
“…However, because most mass gatherings are inherently variable and unique, analysis of our results must carefully examine the specific circumstances of the event for complete interpretation. For example, our MUR of 11.2 PPTT is higher than published reports of medical usage at baseball and football games (MURs of 4.85 PPTT and 6.75 PPTT, respectively), a result that is not surprising given that mobile crowds without well-defined event boundaries have been shown to have higher rates of patient presentations for medical care than fixed-location events with stationary seating (8,9,12). Our results are in contrast to the generally higher MURs at rock concerts, which also have larger proportions of young participants and high rates of drug-and alcohol-associated injuries (11,13,14).…”
Section: Discussioncontrasting
confidence: 52%
“…However, because most mass gatherings are inherently variable and unique, analysis of our results must carefully examine the specific circumstances of the event for complete interpretation. For example, our MUR of 11.2 PPTT is higher than published reports of medical usage at baseball and football games (MURs of 4.85 PPTT and 6.75 PPTT, respectively), a result that is not surprising given that mobile crowds without well-defined event boundaries have been shown to have higher rates of patient presentations for medical care than fixed-location events with stationary seating (8,9,12). Our results are in contrast to the generally higher MURs at rock concerts, which also have larger proportions of young participants and high rates of drug-and alcohol-associated injuries (11,13,14).…”
Section: Discussioncontrasting
confidence: 52%
“…However, the need is to be able to predict medical workload at events, and while this is somewhat dependent on crowd size, 2,3 there are other factors. 8 The predictions made using the Zeitz method not only varied depending on crowd size (and hence day of the week), but also identified differing crowd demographics on different days that had an additional influence on the number of patients. Historical data has shown that medical workload is highest on a mid-week day with half-price admission, even though the largest crowds attend at weekends.…”
Section: Discussionmentioning
confidence: 98%
“…In the United States, the term Medical Usage Rate (MUR) is commonly used, and is defined as the number of first aid attendees per 10,000 event visitors. 4,5 In a nine-year survey at raves in the Netherlands, the average MUR was 79 (range = 59-170). 6 Other countries use Patient Presentation Rates (PPRs), which are calculated as the number of patients per 1,000 event visitors presenting to on-site health care services.…”
Section: Clinical Featuresmentioning
confidence: 99%